Impact of antiviral prophylaxis on EBV viremia and posttransplant lymphoproliferative disorders in solid organ transplant recipients: a systematic review and meta-analysis - Marjan Moghadamnia; Khadijeh Delroba; Shima Heidari; Zahra Rezaie; Simin Dashti-Khavidaki (Virology Journal)
Abstract Introduction Organ transplant recipients face a substantial risk of developing posttransplant lymphoproliferative disorders (PTLD). In over 90% of cases with B‐cell PTLD following solid organ transplantation, the Epstein‐Barr virus (EBV) genome is promptly identified, usually within the initial year. A continuing discussion revolves around the efficacy of antiviral prophylaxis in mitigating the incidence of PTLD in solid organ transplant (SOT) patients. This study aimed to conduct a systematic review and meta-analysis to investigate this issue. Method A comprehensive search was conducted up to December 31, 2023, in databases including PubMed, Embase, and the Cochrane Library for retrospective and prospective studies comparing antiviral prophylaxis effects on EVB viremia and PTLD incidence in SOT recipients. Fixed or random effect models were applied based on the heterogeneity assessed via the I2 statistic, using Stata 16.0 software for data analysis. Results In total, 22 eligible studies involving 13,498 patients were analyzed. Antiviral prophylaxis was associated with a significant reduction in EBV viremia incidence in SOT recipients, as demonstrated in 10 studies (relative risk (RR) 0.69, 95% CI 0.54 to 0.88). The rate of PTLD was significantly lower among those who received antiviral prophylaxis compared to those who did not, as reported in 18 studies (RR 0.77, 95% CI 0.63 to 0.94). No significant difference was observed in the subgroup of high-risk recipients based on EBV serology (RR 1.13, 95% CI 0.72 to 1.78). Additionally, a notable reduction in PTLD incidence was seen in the pediatric subgroup (RR 0.58, 95% CI 0.43 to 0.79) using antiviral prophylaxis, while no significant differences were observed in the subgroup of adults (RR 0.88, 95% CI 0.64 to 1.21). Administration of antiviral prophylaxis can significantly reduce the incidence of PTLD among kidney (RR 0.63, 95% CI 0.46 to 0.87) and heart transplant patients (RR 0.61, 95% CI 0.39 to 0.96). PTLD incidence was significantly reduced among recipients of T-cell depletion or steroid-based immunosuppression using antiviral prophylaxis (RR 0.54, 95% CI 0.39–0.74 and RR 0.55, 95% CI 0.41–0.73, respectively). Conclusion This meta-analysis revealed that administering antiviral prophylaxis to patients after solid organ transplantation reduces PTLD and EBV viremia occurrences, especially among pediatric recipients, individuals undergoing kidney or heart transplantation, and those receiving high-intensity immunosuppression regimens. Key Summary Points Post-transplant lymphoproliferative disorders (PTLD) and other EBV syndromes are among the most serious complications following solid organ transplantation (SOT), primarily due to the necessity for prolonged immunosuppressive therapy. Among the strategies for preventing EBV-related complications, the use of antiviral prophylaxis is a subject of ongoing debate. This systematic review and meta-analysis found that antiviral prophylaxis significantly reduced EBV viremia incidence (risk ratio (RR) 0.69, 95% confidence interval (CI) 0.54 to 0.88) compared to those without prophylaxis. In the sub-analysis related to high-risk EBV serologically mismatched SOT recipients (EBV D+/R-), the result did not show a significant difference in terms of PTLD incidence (RR 1.13, 95% CI 0.72 to 1.78). Antiviral prophylaxis significantly impacted the occurrence of PTLD events among pediatric SOT patients (RR 0.58, 95% CI 0.43 to 0.79), but not among adult patients (RR 0.88, 95% CI 0.64 to 1.21). Antiviral prophylaxis significantly impacted the occurrence of PTLD events among kidney/simultaneous pancreas and kidney (RR 0.63, 95% CI 0.46 to 0.87) and heart (RR 0.61, 95% CI 0.39 to 0.96) transplant patients but not liver  (RR 0.5, 95% CI 0.23 to 1.08) transplant recipients.